Writing from sources - Spatt, Brenda (St. Martin's Press, 1991)
Writing from Sources provides students with a complete guide to the skills of doing research and integrating the results confidently and effectively into their own prose, while providing instructors with all the readings and prompts they need for a complete course in source-based writing.